Pengaruh Intensitas Cahaya Terhadap Variegasi Daun Tanaman Sirih Gading (Epipremnum aureum) - Yasmin Hafizhah Iqbar; Nurmahni Harahap; Halimatus Sakdiyah; Rizka Anggia Dinda; Mursidah Mursidah; Dahlia Dahlia; Riana Sulistianingsih; Andariah Andariah; Ummiyani Ummiyani; Iqbar Iqbar (Universitas Syiah Kuala, 2025)
Leaf variegation (color mixing) is a crucial aesthetic characteristic in ornamental plants, including golden pothos (Epipremnum aureum). Light intensity is hypothesized to influence the variegation levels, though related information remaids limited. This study aims to investigate the effect of varying light intensities on the percentage of color change in golden pothos leaves. The experiment employed a Completely Randomized Design (CRD) with four light intensity treatments: P1 (25%), P2 (50%), P3 (75%), and P4 (100%). Observations were conducted every 5 days over 50 days, with data analyzed using a one-way ANOVA and post-hoc Tukey HSD tests. Results indicated that light intensities of 75% (P3) and 100% (P4) produced significantly higher variegation compared to lower intensities. Between days 30 to 45, P3 (75%) and P4 (100%) achieved the highest color-changes percentages (52.0% and 57.80% respectivly). Statistical analysis revealed significant differences between treatmens, with a high F-value (F = 15.89) demonstrating greater between-group variences than within-group varience. The P-value (<0.05) led to rejection of the null hypothesis (H0). Optimal leaf color change occured under high intensities of 75% and 100%.